Prevalence of canine parvovirus infection in Grand Tunis, Tunisia - Tagorti, Ghada (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The aim of this work was to describe the prevalence of Canine parvovirus type 2 (CPV-2) infection in young dogs of clinical cases presented at the National School of Veterinary Medicine clinic coming from four different governorates of Tunisia, according to epidemiological parameters: sex, breed, age, period, and vaccination status. Materials and methods: 168 domestic juvenile dogs aged between one and seven months were selected based on their pattern of consultation (diarrhea or anorexia with or without vomiting). Data were collected from the database during the period going from September 2012 to July 2013. Results: The overall prevalence of CPV-2 was 32.14% (n=54/168). A total number of 54 young dogs, aging 1 to 7 months, of American Staffordshire terrier, German shepherd, Rottweiler and Spaniel breeds were affected. There was no sex predisposition and German shepherd was the over-represented breed (n=33/54; 61.11%). The prevalence of clinical cases below the three months old was 70.37% (n=38/54) with autumn (n=27/54; 50%) as the most common season of infection. Furthermore, the study showed that 87.04% (n=47/54) of CPV-2 unvaccinated young dogs were positive. Conclusion: This work was a new descriptive study concerning canine parvovirus infection in the Grand Tunis; further studies are required to better characterize the epidemiology of CPV-2 infection in Tunisia. http://doi.org/10.5455/javar.2018.e251